Management of Treatment‐Related Adverse Events with Agents Targeting the MAPK Pathway in Patients with Metastatic Melanoma. (July 2017) - Daud, Adil; Tsai, Katy
Abstract: Tremendous progress has been made in the clinical landscape of advanced‐stage BRAF V600–mutant melanoma treatment over the past 5 years. Targeted therapies that inhibit specific steps of the mitogen‐activated protein kinase pathway have been shown to provide significant overall treatment benefit in patients with this difficult‐to‐treat disease. Combination therapy with BRAF and MEK inhibitors (dabrafenib plus trametinib or vemurafenib plus cobimetinib, respectively) has become standard of care. These agents are administered until disease progression or unacceptable toxicity occurs; thus, some patients may remain on maintenance therapy for an extended period of time, while toxicities may result in early discontinuation in other patients. Because the goal of treatment is to prolong survival with minimal impairment of quality of life, drug‐related adverse events (AEs) require prompt management to ensure that patients derive the best possible benefit from therapy. Proper management depends on an understanding of which AEs are most likely BRAF or MEK inhibitor associated, thus providing a rationale for dose modification of the appropriate drug. Additionally, the unique safety profile of the chosen regimen may influence patient selection and monitoring. This review discusses the toxicity profiles of these agents, with a focus on the most commonly reported and serious AEs. Here, we offer practical guidance derived from our clinical experience for the optimal management of key drug‐related AEs. Implications for Practice: Targeted therapy with BRAF plus MEK inhibitors has become the standard of care for patients with advanced‐stage BRAF V600–mutant metastatic melanoma. To provide optimal therapeutic benefit to patients, clinicians need a keen understanding of the toxicity profiles of these drugs. Prompt identification and an understanding of which adverse events are most likely BRAF or MEK inhibitor associated provide a rationale for appropriate therapy adjustments. Practical recommendations derived from clinical experience are provided for management of key drug‐related toxicities. Abstract : This review provides an overview of the adverse events associated with BRAFi and MEKi in melanoma, with a focus on the most commonly reported and serious adverse events, and offers practical guidance from a clinical perspective for optimal management.